A Gendered Analysis of Poverty among the Employed in South Africa - Makhalima, Jabulile (International Journal of Economics and Financial Issues, 2023)
Poverty is an obstinate issue in South Africa, with many employed individuals still living in poverty. The gender pay gap and employment in low-income jobs are some of the contributing factors to poverty, particularly for women who, on average, earn 30 percent less than men. Women are also more likely to be employed in low-income jobs in the care economy, which offers few benefits, such as domestic work or part-time work. Men, on the other hand, are more likely to be employed in higher-paying jobs in traditionally male-dominated fields. This study seeks to analyse poverty among employed men and women in South Africa using data from the General Household Survey by Statistics South Africa. The results of the regression analysis indicate that women of colour, particularly those with low levels of education and are potentially in precarious employment, are more likely to be poor compared to men. Policies advocating for gender equality in the workforce need to be reinforced while empowering women and men through education and training.